2021
DOI: 10.1175/jcli-d-20-0500.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Regional Asian Summer Monsoons to the Effect of Reduced Surface Albedo in Different Tibetan Plateau Domains in Idealized Model Experiments

Abstract: The thermal effect of entire Tibetan Plateau (TP) tends to strengthen the South Asian summer monsoon (SASM); however, how does this monsoon component respond to the thermal conditions of different TP domains? How do the thermal condition of entire TP influences other monsoons including the East Asian summer monsoon (EASM) and the Southeast Asian summer monsoon (SEASM)? These questions are addressed by conducting an experiment with the CESM, which is forced by reducing the surface albedo over the plateau by hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Theoretical and modeling studies suggested that the relative importance of the thermal and mechanical forcing, which is not the focus of this study, is very sensitive to the strength of the basic flow (Held & Ting, 1990; Held et al., 2002). Moreover, a latest study revealed that the monsoon responses to different heating regions of TP are quite different (Lu et al., 2021). Overall, the TP is an important mechanical and thermal forcing that adjusts the energy and hydrological cycle in the Earth system (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and modeling studies suggested that the relative importance of the thermal and mechanical forcing, which is not the focus of this study, is very sensitive to the strength of the basic flow (Held & Ting, 1990; Held et al., 2002). Moreover, a latest study revealed that the monsoon responses to different heating regions of TP are quite different (Lu et al., 2021). Overall, the TP is an important mechanical and thermal forcing that adjusts the energy and hydrological cycle in the Earth system (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to local circulation, the PV budget view can also be used to investigate the dynamics underlying the remote influences of the TP, especially its surface PV source, on weather and climate. In particular, previous studies suggested that the TP influences the climate of upstream Eurasia and Africa via zonal‐vertical circulation cells and Rossby waves (Lu et al ., 2018; Nan et al ., 2019; Liu et al ., 2020b) and the climates of the Indian Ocean, downstream Asia, Pacific Ocean, North America, and Atlantic Ocean via Rossby waves and meridional‐vertical circulation cells (Wu et al ., 2007; Zhao et al ., 2007; Park et al ., 2013; Sun et al ., 2019; Yang et al ., 2020; You et al ., 2020; Liu et al ., 2020a; Lu et al ., 2021); tropical cyclones (Baldwin et al ., 2019); and weather, including synoptic temperature variability in winter around the TP (Lutsko et al ., 2019), Eurasian heatwaves in summer (Wu et al ., 2015b), and downstream severe weather in China (Wu et al ., 2020; Ma et al ., 2022)…”
Section: Discussionmentioning
confidence: 99%
“…However, the link between Homo erectus and Acheulean bifacial technology is complex [86] and bifaces are notably absent from several other assemblages associated with Homo erectus. Stone tools recovered from Zhoukoudian represent typical core-and-flake industries without bifaces [87][88][89][90][91]. Artifacts were not directly recovered at Kocabaş, Anatolia, although nearby lithics from Bozyer, Anatolia were suggested to be manufactured by Homo erectus [92].…”
Section: Taxonomy Of Early Paleolithic Toolmakersmentioning
confidence: 99%